The XXL Survey: XXIX. GMRT 610 MHz continuum observations - Smolcic, V.; Intema, Hubertus; Šlaus, B.; Raychaudhury, S.; Novak, M.; Horellou, C.; Chiappetti, L.; Delhaize, J.; Birkinshaw, M.; Bondi, M.; Bremer, M.; Ciliegi, P.; et al. (EDP Sciences, 2018)
We present the 25 square-degree GMRT-XXL-N 610 MHz radio continuum survey, conducted at 50 cm wavelength with the Giant Metrewave Radio Telescope (GMRT) towards the XXL Northern field (XXL-N). We combined previously published observations of the XMM-Large Scale Structure (XMM-LSS) field, located in the central part of XXL-N, with newly conducted observations towards the remaining XXL-N area, and imaged the combined data-set using the Source Peeling and Atmospheric Modeling (SPAM) pipeline. The final mosaic encompasses a total area of 30:4 square degrees, with rms <150 µJy beam-1 over 60% of the area. The rms achieved in the inner 9.6 square degree area, enclosing the XMM-LSS field, is about 200 µJy beam-1, while that over the outer 12.66 square degree area (which excludes the noisy edges) is about 45 µJy beam-1. The resolution of the final mosaic is 6.5 arcsec. We present a catalogue of 5434 sources detected at =7 × rms. We verify, and correct the reliability of, the catalog in terms of astrometry, flux, and false detection rate. Making use of the (to date) deepest radio continuum survey over a relatively large (2 square degree) field, complete at the flux levels probed by the GMRT-XXL-N survey, we also assess the survey's incompleteness as a function of flux density. The radio continuum sensitivity reached over a large field with a wealth of multi-wavelength data available makes the GMRTXXL- N 610 MHz survey an important asset for studying the physical properties, environments and cosmic evolution of radio sources, in particular radio-selected active galactic nuclei (AGN).